Grandiose Narcissism and Trait Anxiety among Adolescents: The Mediating Role of Perfectionism when Self-esteem is controlled - Şahin, Ezgi Ekin; Altinok, Ahmet; Duy, Baki (Anales de Psicología / Annals of Psychology, 2022)
It seems quite interesting that during adolescence anxiety levels can spiral out of control. This is due to several factors; one of the possible determinants is personality traits such as narcissism. Contrary to high self-esteem being a predictive factor of mental health, narcissism needs self-esteem in order to be beneficial for a person. Therefore, as two factors of personality traits, self-esteem and narcissism need to be distinguished from each other. Narcissistic individuals try to meet their affirmation needs by setting perfectionistic goals and significant relationships between perfectionism dimensions and anxiety has been revealed in the related literature. Using a structural equation modeling, this study investigated the mediation role of perfectionism dimensions in the relationships between grandiose narcissistic personality trait and trait anxiety when self-esteem was controlled. A sample of 338 adolescents (192 females, 146 males, mean age = 15.84 years, SD = 1.01) from five high schools participated in the study. The participants completed the instruments including the Demographic Information Form aimed to gather personal information, the Rosenberg Self Esteem Scale, the trait anxiety dimension of the State-Trait Anxiety Inventory, the Child and Adolescents Perfectionism Scale, and the Narcissistic Personality Inventory. Findings revealed that adaptive perfectionism mediated the relationship between grandiose narcissism and trait anxiety when self-esteem was controlled. This study indicates that practitioners working with adolescents should focus on interventions, which aimed to decrease perfectionistic tendencies of adolescents.